Tra??os de personalidade e perfil psicol??gico de g??nero em idosas obesas - Pra??a, Isabella Reis (2016)
The personality may be defined as the stable characteristics which make the single individual and that influences the way to react to events of life. So know the specific groups personality traits enables more and more health professionals. Therefore, the objective of this study was to evaluate Personality Traits and Psychological Profile Gender of obese older women and compare these variables with lean older, eutrophic and overweighed. It is a descriptive and comparative cross-sectional survey, which involved 135 elderly residents in the Federal District, with a mean age 69.40 ?? 6.31 years. For data collection were used a sociodemographic questionnaire, the Inventory of the Big Five Personality Factors, the Feminine Inventory of the Self Gender schemes and performed a physical evaluation (body weight and height). The results showed that high levels of Kindness (4.65 ?? 0.87), extroversion (3.68 ?? 0.82) and aperture (3.38 ?? 0.98) and low levels of neuroticism (2.95 ?? 0 , 81) and Conscientiousness (2.60 ?? 0.63) and they do not differ with respect to body composition (p> 0.05). With regard to psychological gender profile (heteroesquematics male, female and isoesquematics not differ with respect to body composition (lean, normal weight, overweight and obese). It follows therefore that personality traits are not related to body composition of the women studied, because thin elderly, normal-weight, overweight and obese have the same characteristics in personality (high kindness values, extroversion and openness and low levels of neuroticism and conscientiousness) and that obesity in elderly women is not related to high femininity values.